Personalized treatment of obesity complicated with obstructive sleep apnea syndrome (Ожирение и метаболизм, 2014)
Obstructive sleep apnea (OSA) and obesity are mutually burdening clinical conditions. Weight loss is quite effective for the control of breathing disorders during sleep, but the impact of OSA treatment on the dynamics of body weight in obese patients remains poorly studied. Presented clinical case features a significant reduction in body weight in a patient with morbid obesity complicated by severe OSA with contemporary approach and without CPAP therapy due to high patient adherence to therapy and absence of comorbidities.